The Tourism Office's Role In Developing The Lowita Beach Tourism Awareness Group's Competence - Ade Safitri (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The aim of this study is to identify the role of the tourism office in developing the competence of the tourism awareness group in Lowita Beach, Pinrang Regency. It also aims to explore strategies used to enhance their competencies. Methodology: This study employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation. The research was conducted at Lowita Beach, Pinrang Regency. Data analysis involved data reduction, data presentation, and drawing conclusions. Informants included tourism office staff and members of the tourism awareness group. Main Findings: The Tourism Office of Pinrang Regency has implemented various strategies to develop the competence of the tourism awareness group in Lowita Beach, including training in technical, theoretical, and conceptual skills. However, participation and support from the Youth and Sports Division remain insufficient. While progress has been made, further innovation and capacity building are needed to meet national tourism village standards. Novelty/Originality of this study: This study offers an in-depth look at the actual role and strategic implementation of local tourism governance in developing community-based tourism actors. It highlights the importance of structured competency development for sustainable tourism growth and contributes new insights on how local government support influences tourism village success.